Modulação da resposta celular e da via de sinalização do IFN-y pela glucuronoxilomanana (GXM) de Cryptococcus neoformans - ARAÚJO, Alessandra da Silva (2015)
Cryptococcosis is an systemic fungal infection caused by Cryptococcus neoformans and Cryptococcus gattii, encapsulated yeasts, affecting mainly immunocompromised and immunocompetent individuals respectively. Infection occurs after inhalation of microorganism’s propagules dispersed in the air, which subsequently penetrates into the lungs, with a tendency to invade the central nervous system. The polysaccharide capsule is the main virulence factor of this fungus, composed mostly of glucuronoxilomanan (GXM), an outer surface component, with great immunogenic potential that appears to be essential in protecting these fungi against host defenses. In this work we evaluate the immunoregulatory effects of GXM obtained from C. neoformans on polymorphonuclear (PMN) and peripheral blood human mononuclear cell (PBMC) response to recombinant human IFN-γ. Initially, we evaluated the effect of GXM on CXCL10 production in cell culture supernatants and subsequently, the intracellular chemokine production in PMNs and PBMCs by flow cytometry. The results showed that GXM modulates PMN and PBMC response to IFN-γ by reducing CXCL10 production. The evaluation of IFN-γ receptor alpha chain (IFN- γR1/CD119) expression by flow cytometry revealed that GXM reduces the expression of this receptor. Finally, human monocytes significantly reduced STAT1 phosphorylation after in vitro incubation with GXM. Thus, our study demonstrated that GXM from C. neoformans interferes with cellular response to IFN-γ and its signaling pathways in human PMN and PBMC. The data obtained in the present study increases the understanding of pathogenic mechanisms used by C. neoformans to escape host’s immune system, and may contribute to development of new therapeutic strategies for cryptococosis.